THE EVOLUTION OF SPEECH THERAPY TECHNIQUES: INNOVATIONS, CHALLENGES, AND FUTURE TRENDS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article explores "The Evolution of Speech Therapy Techniques: Innovations, Challenges, and Future Trends" as a comprehensive exploration of the historical development, current practices, and potential advancements in the field of speech therapy. The authors provide an in-depth analysis of the evolution of speech therapy techniques, highlighting the innovative approaches that have emerged over time. They also address the challenges faced by speech therapists, such as adapting to new technologies and meeting the diverse needs of clients. Furthermore, the article delves into the future trends of speech therapy, offering insights into potential advancements and opportunities for growth in the field. This annotation serves as a valuable resource for speech therapists, educators, researchers, and anyone interested in the evolving landscape of speech therapy techniques.